Analisis Pendapatan Masyarakat dari Adanya Destinasi Wisata Air Terjun Lubuak Bulan (Studi Kasus Air Terjun Lubuak Bulan Kecamatan Mungka Kabupaten 50 Kota) - M. Handiko Firdaus; Cahya Agung Mulyana (ARZUSIN, 2026)
Tourism sector development has received attention in various studies because it is considered capable of promoting the economic growth of local communities. However, research specifically examining changes in community income before and after the management of the Lubuak Bulan Waterfall Tourism Destination in Nagari Simpang Kapuak, Mungka Subdistrict, Lima Puluh Kota Regency remains limited. This study aims to analyze community income from the existence of the Lubuak Bulan Waterfall Tourism Destination. This study used a qualitative approach with a case study design, involving nine informants selected through purposive sampling. Data were collected through observation, semi-structured interviews, documentation, and literature study, and were then analyzed using interactive analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that the existence of the Lubuak Bulan Waterfall Tourism Destination had an impact on increasing community income through the development of food and beverage businesses, stalls, vehicle parking services, and tour guide services. In addition, the increase in community income was strongly influenced by the number of tourist visits and had not been experienced evenly by all communities around the tourist area. The conclusion of this study affirms that community involvement in tourism management is an important factor in creating a more equitable and sustainable improvement in economic welfare. These findings contribute to the development of studies on community-based tourism and the multiplier effect in the context of local community economies, while also providing practical implications for local governments and tourism managers in formulating more inclusive and sustainable tourism policies.